2011
DOI: 10.1121/1.3569700
|View full text |Cite
|
Sign up to set email alerts
|

Distortion products and backward-traveling waves in nonlinear active models of the cochlea

Abstract: This study explores the phenomenology of distortion products in nonlinear cochlear models, predicting their amplitude and phase along the basilar membrane. The existence of a backward-traveling wave at the distortion-product frequency, which has been recently questioned by experiments measuring the phase of basilar-membrane vibration, is discussed. The effect of different modeling choices is analyzed, including feed-forward asymmetry, micromechanical roughness, and breaking of scaling symmetry. The experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…Furthermore, theoretical evidence continues to support the slow-wave hypothesis for retrograde transmission of DPs (Vetešník et al, 2006a;Shera et al, 2007;Frosch, 2009;Zhang and Mountain, 2009;Sisto et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, theoretical evidence continues to support the slow-wave hypothesis for retrograde transmission of DPs (Vetešník et al, 2006a;Shera et al, 2007;Frosch, 2009;Zhang and Mountain, 2009;Sisto et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…The result is a measurable interference pattern near CF. As discussed elsewhere (Sisto et al, 2011;de Boer et al, 2011;Vetesnik and Gummer, 2012), analogous reasoning explains why studies that have used distortion products to look for reversetraveling waves on the BM have had difficulty finding them (e.g., Ren, 2004;He et al, 2008;de Boer et al, 2008)-the reverse wave, although present, is swamped out by the forward wave that subsequently arises from reflection at the stapes and is then boosted by the cochlear amplifier.…”
Section: A Bm Ripples and Standing Wavesmentioning
confidence: 99%
“…They found that forward propagation waves could be generated by the DP if the activity was sufficiently broad and the reflectivity of the stapes was realistic. Although the model of Sisto et al 22 is incomplete as it does not admit fast waves in the same way as a more complete two-duct model does (either an elegant post-processing step, as in Yoon et al 3 or our more straightforward approach would be needed to include this effect), it nicely points out that when activity is present, an internal force can generate forward traveling waves. Our model predicts such a situation when the best place of the stimulus frequency is apical to the force (see Fig.…”
Section: E Implications On the Dpoaementioning
confidence: 99%
“…The forcing at the DP frequency arising from the nonlinear interaction of the primaries is likely more complicated (with variable phases and amplitudes). Sisto et al 22 were able to control the width of the region of the DP force generation in a nonlinear cochlear model by varying the model parameters. They found that forward propagation waves could be generated by the DP if the activity was sufficiently broad and the reflectivity of the stapes was realistic.…”
Section: E Implications On the Dpoaementioning
confidence: 99%
See 1 more Smart Citation